Analysis of vegetable purchasing patterns in supermarkets using association rule - Kasmawaru Kasmawaru; Imran Djafar; Muh Rafli R; Rachmat Rasyid; Muh Yusuf (Jurnal Mantik, 2023)
One data mining technique for identifying associative rules between a set of elements is association analysis, often known as association rule mining. Understanding the likelihood that a consumer will purchase bread and milk together is an example of an associative rule from examining purchases made in a supermarket. Supermarket operators can use this information to plan their product placement or create marketing campaigns that use discount coupons for specific product pairings. The use of association analysis to examine the contents of supermarket shopping baskets helped make it well-known. Another name for association analysis is market basket analysis. Perform a multiplication of the numerous rules acquired by Support and Confidence, where the latter should be at least 80%.